The mind of Jihad - Murawiec, Laurent (Cambridge Univ. Press, 2008)
Introduction -- "We love death" -- "An elite of amoral supermen" -- The gnostic mahdi -- Manichean tribalism -- The odd pedigree of modern jihad -- The mutated virus : "Islamic revolution" -- Jihad as terror -- Conclusion. - Includes bibliographical references and index